Thomas & friends : Teman baru Belle / W. Awdry; Penerjemah, Shelomi Angeli; Editor, Editor, Tessa Febiani dan Dwi Kartika Wardhani - AWDRY, W.; SHELOMI Angeli; TESSA Febiani; DWI Kartika Wardani (Erlangga, 2012)
24 hlm. : Ilus. ; 23 cm.